Sustainability assurance: Insights into assured sustainability-related information of the Top 100 companies listed on the ASX and JPX - Nkosi, Nompumelelo Lizette (University of the Witwatersrand, Johannesburg, 2024)
There is a lack of consensus and ambiguity on the currently adopted standards on sustainability and the assurance thereof which has led to variations in the subject matter assured, criteria used, and the type of assurance provided. This study aims to broaden the extant body of literature related to the assurance of sustainability-related information and provide new insights that can guide future research. The study aims to investigate the sustainability-related assurance practices and reports for the top 100 companies listed on the Australian Stock Exchange (ASX) and the Japan Stock Exchange (JPX). Data was collected for 113 companies (52 companies for ASX and 61 companies for JPX). A content analysis of the audit report and the sustainability-related information reports was used to collect data based on a disclosure checklist. The data was analysed and reported on using descriptive statistics and inferential statistics. Based on the results from the statistics performed, it was noted that there is a difference in the number of subject matter items assured in a category however there is congruence in the subject matter items. This provides evidence of mimetic isomorphism and highlights how companies are using specific subject matter items as an important signal to the market to indicate the credibility of the sustainability reports. Albeit the majority of the assurance provided are limited assurance engagements, some subject matter characteristics should preclude assurance. This finding supports prior research that non- financial assurance engagements do not provide sufficient value to the stakeholders. In addition, it was found that there is variability in the assurance providers based on jurisdiction with financial auditors (traditional auditors) found to be dominate in the ASX and sustainability auditors gaining ground in the JPX. Sustainability auditors could add to the complexity and confusion of the assurance process due to being less likely to have professional training on assurance which allows the engagement of financial auditors by companies to be a signal for stakeholders.
A research report submitted in fulfillment of the requirements for the Master of Commerce, In the Faculty of Commerce, Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Sustainability reporting; sustainability assurance; subject matter and criteria; Australia; and Japan; SDG-12: Responsible consumption and production; SDG-13: Climate action